The Influence of Interpersonal Communication and Workplace Friendships on Employee Job Satisfaction in Public Organizations - Asniwati Asniwati; Fitriani Latief (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the influence of interpersonal communication and workplace friendships on employee job satisfaction in a public-sector organization.. Research Method: A quantitative survey approach was employed involving 80 employees of the South Sulawesi Provincial Office of Communications, Information Technology, Statistics, and Cryptography. Data were collected through questionnaires and analyzed using SPSS 23, including validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis. Results and Discussion: The results indicate that interpersonal communication has a positive but insignificant effect on employee job satisfaction. In contrast, workplace friendships have a positive and significant effect on job satisfaction. These findings suggest that supportive social relationships, trust, and friendship among colleagues contribute more strongly to employee satisfaction than communication processes alone. The study highlights the importance of workplace social dynamics in shaping positive employee attitudes within public organizations. Implications: Public organizations should foster supportive workplace relationships through collaboration, team-building activities, and programs that encourage social interaction and peer support to enhance employee satisfaction. Originality: This study provides empirical evidence that workplace friendships are a stronger predictor of job satisfaction than interpersonal communication, offering new insights into the role of informal social relationships in public-sector workplaces.